2017
DOI: 10.1017/s1431927616012654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Analysis Conditions for Laser-Pulsed Atom Probe Tomography: Example of Cemented Tungsten Carbide

Abstract: Cemented tungsten carbide has been analyzed using laser-pulsed atom probe tomography (APT). The influence of experimental parameters, including laser pulse energy, pulse repetition rate, and specimen base temperature, on the acquired data were evaluated from different aspects, such as mass spectrum, chemical composition, noise-to-signal ratio, and multiple events. Within all the applied analysis conditions, only 1 MHz pulse repetition rate led to a strong detector saturation effect, resulting in a largely bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
0
18
1
Order By: Relevance
“…In our data, the M/DM 10 peak parameter increases with laser energy. This trend is opposite to the trend observed in zircon and rutile (Saxey et al 2018, Verberne et al 2019 but is similar to what is observed in tungsten carbide (Peng et al 2017) although it is unclear what effects the laser stepping protocol may have on peak shape. In monazite, we demonstrated that at higher laser power, the field at the apex of the specimen is reduced, suggesting that less spontaneous evaporation would occur between pulses and this could be the explanation for the narrower peaks.…”
Section: Effect Of Instrument Parameters On Data Qualitycontrasting
confidence: 65%
“…In our data, the M/DM 10 peak parameter increases with laser energy. This trend is opposite to the trend observed in zircon and rutile (Saxey et al 2018, Verberne et al 2019 but is similar to what is observed in tungsten carbide (Peng et al 2017) although it is unclear what effects the laser stepping protocol may have on peak shape. In monazite, we demonstrated that at higher laser power, the field at the apex of the specimen is reduced, suggesting that less spontaneous evaporation would occur between pulses and this could be the explanation for the narrower peaks.…”
Section: Effect Of Instrument Parameters On Data Qualitycontrasting
confidence: 65%
“…To achieve similar Si field evaporation, the LEAP 3000X HR required approximately a factor of 25 higher laser energy per pulse than the LEAP 4000X HR, in comparison to a factor of 15 difference reported for similar tools previously . An additional comparative analysis of a LEAP 3000X HR and a LEAP 5000X HR, which uses nominally the same laser system as a LEAP 4000X HR, recently showed a similar factor of 12 difference . Note that the calibration is imperfect as it is not possible to separate differences in laser spot size from laser wavelength and other uncontrollable experimental parameters (e.g.…”
Section: Methodsmentioning
confidence: 71%
“…Laser-assisted field evaporation can provide ready access to diverse types of molecular cations, which can already be noticed from literature. For instance, in the analysis of oxides, 5862 carbides, 35,43,55 and nitrides, 50,5254,63 oxygen, carbon, nitrogen, as well as (non)metal–oxygen, (non)metal–carbon, (non)metal–nitrogen cluster cations were observed. Large organic molecular ions were detected when measuring biological materials.…”
mentioning
confidence: 99%